Experts Online : An Analysis of Trading Activity in a Public Internet Chat Room - Bruce Mizrach; Susan Zhang Weerts (Rutgers University, Department of Economics, 2004)
We analyze the trading activity in an Internet chat room with approximately 1,300 participants. Traders make posts in real time about their activities. We find these traders are more skilled than retail investors analyzed in other studies. 55% make profits after transaction costs, and they earn 153 per trade. Traders hold their winners 25% longer than their losers. They have statistically significant alphas of 0.41% per day after controlling for the Fama-French factors and momentum. 38% of profits persist in the next year. Traders improve their skill over time, earning an extra 189 per month for each year of trading experience. They also gain expertise in trading particular stocks. Traders who raise their Herfindahl index by 0.1 raise their profitability by 46 per trade. 42% trade both long and short, with equal success rates, and almost double the profit per trade when short.
Keywords: G20; G14; 330; behavioral finance; day trading; familiarity bias; disposition effect; experts; Wertpapierhandel; Internet; Anlageverhalten; Vereinigte Staaten